The concept of Islamic work ethic: An analysis of some salient points in the prophetic tradition - Ahmad, Shukri; Owoyemi, Musa Yusuf (Centre for Promoting Ideas, 2012)
The issue of work ethics and value systems associated with work has captured the attention of scholars,for the past seven decades. Most discussions about these topics have been concerned with Judeo-Christian contributions and, to a large extent, have been carried out in Western societies.Despite the fact that many other religions and ethnic groups have achieved prosperity and tremendous economic advancement during part of their history, their contributions have been almost totally ignored in management literature and in the discourse on work ethics.The Islamic view of work and ethical considerations have either been misunderstood or not widelv studied in the field of organization studies.Thus, bearing the above in mind, this paper analyzes the concept of work ethics from the prophetic tradition. Although admitting that Hadith should be part of understanding the Qur'an, nonetheless, this research focuses primarily on the Hadith by deliberately separating the treatment of the concept of work ethics in Hadith literature,from the Qur'an.To,fulfill its aim, it examines some characteristics and attitudes which are central to Islamic work ethics, such as attitudes to wealth, attitudes to livelihood, attitudes to time and attitudes to leisure. Through this, it came to the conclusion that the concept of work ethics is part and parcel of the Islamic tradition when properlv analyzed, especially through the Hadith traditions, and it can serve its purpose in the workplace as is the case in the Judeo-Christian traditions.